ANALYSIS OF THE EFFECT OF BYPASS RATIO ON PERFORMANCE ENGINE CFM56-5A1 IN CRUISING CONDITIONS - opri surya yustinoto (Institut Teknologi Dirgantara Adisutjipto, 2020)
The value of engine performance is known to decrease and increase with increasing and decreasing variation of the value of the parameter bypass ratio, so that if the value of these parameters is greater, then the fuel consumption when the aircraft operates will be less and the thrust will decrease. In addition to changing the value of the specific fuel consumption due to the influence of the bypass value, variations in altitude are also very influential where the higher the aircraft, the resulting specific fuel consumption value will be smaller